2016
DOI: 10.1039/c6ra21208e
|View full text |Cite
|
Sign up to set email alerts
|

Novel super-toughened bio-based blend from polycarbonate and poly(lactic acid) for durable applications

Abstract: Novel high-performance bio-based PC/PLA blends are created via high-temperature reactive blending, using targeted toughening of the brittle phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…This highly reactive compound prevents the excessive decrease in the polymer molecular weight through the branching of the polymer chains. In the case of the presented research work, the used modifier was Joncryl 4368C, whose effectiveness has been confirmed by numerous studies, 38,39 including those on PC. In the case of the described studies, a 0.5% addition was determined experimentally and corresponded with the manufacturer recommendations.…”
Section: Processing Stability: Pc Matrix Degradationsupporting
confidence: 55%
See 2 more Smart Citations
“…This highly reactive compound prevents the excessive decrease in the polymer molecular weight through the branching of the polymer chains. In the case of the presented research work, the used modifier was Joncryl 4368C, whose effectiveness has been confirmed by numerous studies, 38,39 including those on PC. In the case of the described studies, a 0.5% addition was determined experimentally and corresponded with the manufacturer recommendations.…”
Section: Processing Stability: Pc Matrix Degradationsupporting
confidence: 55%
“…Joncryl ADR 4368 (a product of BASF, Ludwigshafen, Germany) is commonly used as a multifunctional reactive copolymer with its high epoxy equivalent weight of 285 g/mol. This type of CE is partially miscible in many polyesters, including Poly(ethylene terephthalate) (PET), Poly(lactic acid) (PLA), and PC, and has been reported several times . The typical application of this type of reactive modifier is its use during the processing of recycled materials, where the degradation issues caused by increased moisture concentration are a very common problem.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of melt blending technology results from its low cost; typically this method of polymer modification does not require any additional treatments and is conducted at the stage of the preparation of polymer compositions, where the composition of matrix polymers is compounded with other additives, modification. The first one involved the introduction of a rubbery impact modifier, ethylene/butyl acrylate/glycidyl methacrylate terpolymer (E/BA/GMA), a material which has already been successfully applied to PLA-based blends [14,21,42] and POM/PLA blends [31]. The second method was based on the use of reactive blending and phase compatibilization using epoxy functionalized oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymers such as polylactic acid, polyglycolic acid, polylactic‐co‐glycolic acid, and poly(ε‐caprolactone) (PCL) can undergo hydrolysis and have all been used to fabricate tissue engineering scaffolds. However, these materials lack a proper elasticity matching that of living tissue . Polyurethane (PU) is one of the most widely used polymers in biomedical applications because of its good biocompatibility and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%